An Examination of Oil Palm Flowering: Molecular Biology and Anatomical Analysis - Syed Alwee, Sharifah Shahrul Rabiah (1998)
Flowering is an important part of oil palm crop production The ability to control flowering will be economically beneficial to the oil palm industry Before control can be exerted, factors that influence flowering must be studied at the level of physiology, biochemistry and molecular biology The morphological aspects of oil palm flower development were examined by light and electron microscopy. In doing so, oil palm flower development was able to be partially staged for future reference to determine the expression pattern of flower-predominant genes. Protein analysis was carried out to identify unique proteins that are expressed in the vegetative meristem or the floral meristem. Three proteins were identified, the presence or absence of which could be associated with the conversion of a vegetative meristem into an inflorescence meristem. Histological studies made on the flowers produced by the inflorescence meristem revealed that these flowers were not true flowers. These flower-like structures were not found to have any reproductive structures and only contained bracts. This reflected that in vitro, under high cytokinin growth condition, the conversion of inflorescence meristem to a floral meristem is disrupted. Flower-predominant clones were isolated from an oil palm male flower cDNA library by a differential screening procedure. Four out of 10 floralpredominant clones were characterized. Clone 68 has homology to cytochrome P450 while clone 65, 70 and 72 do not have any significant homology with any known functional genes but their characteristics showed that clones 65 and 70 could be a glycoprotein and clone 72, a protein kinase. However, the functions of these genes in oil palm flowering are still unconfirmed.